Robust and nonlinear control of interconnected systems - Xie, Shoulie. (2008)
This thesis presents the results of research work on robust and nonlinear control of un-certain interconnected systems. The thesis is divided into two parts, one is on control problems of linear interconnected systems; and the other on control of nonlinear inter-connected systems. The systems under consideration include deterministic and stochastic systems.